Knowledge-based capital in a set of Latin American countries: The LA KLEMS-IDB project - Eva Benages; Matilde Mas (Inter-American Development Bank (IDB), 2021)
This paper presents the framework and methodology for the economic valuation of the knowledge-based economy in five Latin American (LA) countries, namely Costa Rica, El Salvador, Mexico, Peru and the Dominican Republic, for which a new database (IDB-Ivie, 2020) has recently been released. It uses an alternative approach to measuring the knowledge intensity of economies as to those based on the aggregation of industries according to selected indicators such as research and development (R&D) expenditure or labor force skills. Instead, we follow an economic approach rooted in the growth accounting methodology, determining the contribution of each individual factor of production (capital and labor) according to the prices of the services it provides. This methodology will be applied to the above-mentioned LA countries, and to the United States and Spain, which are used as benchmarks. Data are available for the period 1995-2016.
Keywords: O33; O47; 330; Knowledge economy; Growth accounting; Capital services; Human capital; Fiscal rules; Public investment; Fiscal policy; Brazil